Modification of the supramolecular structure of [(thione)IY] (Y = Cl, Br) systems by cooperation of strong halogen bonds and hydrogen bonds1. Issue 13 (7th April 2015) - Koskinen, L.; Hirva, P.; Hasu, A.; Jääskeläinen, S.; Koivistoinen, J.; Pettersson, M.; Haukka, M.
<x xml:space="preserve">Abstract</x> Strong halogen bonds and hydrogen bonds cooperated to control the supramolecular structures of [(thione)IY] (Y = Cl, Br) compounds.